Embedded Digital Filter System on Microcontroller to Reduce Noise in Single Lead Electrocardiography Design - Setiawan, Singgih Yudha; Miftahul Maghfiroh , Anita (Jurnal Teknokes, 2025)
The background of this research focuses on improving the quality of ECG signals which are often disturbed by noise, which can affect the accuracy of cardiac diagnosis. The main objective of the research is to show the effectiveness of the 6th order IIR (Infinite Impulse Response) filter in reducing noise in the ECG signal and increasing the Signal-to-Noise Ratio (SNR) value. This research contributes by applying advanced filtering methods to embedded systems and analyzing the results using the Fast Fourier Transform (FFT) to transmit frequency spectrum signals. The results showed that the use of a 6th order IIR filter resulted in an increase in SNR of 15.97 dB, indicating a significant improvement in the cleanliness of the ECG signal after the filtering process. FFT confirmed that this filter effectively reduced noise and clarified component frequency signals, supporting the success of the method used. The conclusion of this study is that the 6th order IIR filter is very effective in improving ECG signal quality by reducing noise and increasing diagnostic accuracy. Implications of these results include the potential use of this technology in medical devices for more accurate cardiac monitoring, as well as the need for further research to explore other screening methods and validation in various clinical settings. This research opens up opportunities for the development of better filter technology and integration in medical systems to improve patient care outcomes.